Disentangling the Effects of the 2018-2019 Tariffs on a Globally Connected U.S. Manufacturing Sector - Flaaen, Aaron; Pierce, Justin (The Review of Economics and Statistics, 2024)
This paper estimates the relationship between the U.S. tariff increases of 2018-2019 and outcomes in domestic manufacturing. Despite being intended to boost manufacturing activity, we find U.S. industries more exposed to tariff increases experience relative reductions in employment, as a small positive effect from import protection is offset by larger negative effects from rising input costs and retaliatory tariffs. Higher tariffs are also associated with relative increases in producer prices due to rising input costs. Lastly, we document broader labor market impacts, as counties more exposed to rising tariffs exhibit relative increases in unemployment and declines in labor force participation.